Evidence for exposure of asymptomatic domestic pigs to African swine fever virus during an inter‐epidemic period in Zambia. Issue 6 (2nd June 2020) - Chambaro, Herman M.; Sasaki, Michihito; Sinkala, Yona; Gonzalez, Gabriel; Squarre, David; Fandamu, Paul; Lubaba, Caesar; Mataa, Liywalii; Shawa, Misheck; Mwape, Kabemba E.; Gabriël, Sarah; Chembensofu, Mwelwa; et al.
Abstract: African swine fever (ASF) causes persistent outbreaks in endemic and non‐endemic regions in Zambia. However, the epidemiology of the disease is poorly understood, particularly during the inter‐epidemic periods. We conducted surveillance for ASF in asymptomatic domestic pigs and soft ticks in selected Zambian provinces. While serum samples ( n  = 1, 134) were collected from crossbred pigs from all study sites between 2014 and 2017, whole blood ( n  = 300) was collected from both crossbred and indigenous pigs in Eastern Province (EP) in 2017. Soft ticks were collected from Mosi‐oa‐Tunya National Park in Southern Province (SP) in 2019. Sera were screened for antibodies against ASF by ELISA while genome detection in whole blood and soft ticks was conducted by PCR. Ticks were identified morphologically and by phylogenetic analysis of the 16S rRNA gene. Seroprevalence was highest in EP (50.9%, 95% CI [47.0–54.9]) compared to significantly lower rates in SP (2.9%, 95% CI [1.6–5.1]). No antibodies to ASFV were detected in Lusaka Province. In EP, the prevalence of ASFV genome was 11.7% (35/300), significantly higher (OR = 6.2, 95% CI [2.4–16.6]) in indigenous pigs compared to crossbred pigs. The pooled prevalence of ASFV genome in ticks was 11.0%, 95% CI [8.5–13.9]. Free‐range husbandry system was the only factor that was significantly associated with seropositive ( p  < .0001, OR = 39.3) and PCR‐positive results ( p  < .001, OR = 5.7). Phylogenetically, based on the p72 gene, ASFV from Ornithodoros moubata ticks detected in this study belonged to genotype I, but they separated into two distinct clusters. Besides confirming ASF endemicity in EP and the presence of ASFV‐infected ticks in SP, these results provide evidence for exposure of domestic pigs to ASFV in non‐endemic regions during the inter‐epidemic period.